Experiences of participants in ETEC controlled human infection model studies - Bettina Wunderlich; Kathryn Chang; Jessica L. Schue; Lawrence H. Moulton; Nancy Kass; Ruth A. Karron; Kawsar R. Talaat (PLoS ONE, 2025)
Background Controlled human infection model (CHIM) studies raise ethical issues due to intentional exposure of healthy volunteers to a pathogen. In this study we examine the experiences of participants who have chosen to participate in enterotoxigenic Escherichia coli (ETEC) CHIM studies in a single research center. Methods An interviewer-administered paper-based survey was conducted with participants in an ETEC CHIM study at the Center for Immunization Research (CIR) from 2009–2020. We analyzed participant characteristics, study experiences, and perceived risks before and after study participation. Results 48 participants in ETEC studies were interviewed. 81.3% of participants identified as Black or African American, 43.8% completed at most high school, and 39.6% of interviewees had incomes of less than $18,500 in the last year. Most respondents enjoyed participating and were glad they joined. Participants most frequently identified interactions with research staff, compensation, and food quality as the most positive aspects of their experiences. There was a significant reduction in the perceived risk of the ETEC study after completing participation compared to perceived risk before joining. Conclusions Despite the expected side effects of ETEC CHIM studies, most participants believe the benefits outweigh the risks and would participate again.